The role of penicillin major and minor determinants in skin testing for suspected penicillin hypersensitivity - Daniel G. Lapirow, MD; Sara Vogrin, MBiostat; Joseph F. De Luca, MBBS; Jack D. Godsell, MBBS; Jason A. Trubiano, MBBS, PhD (World Allergy Organization Journal)
Background: In the evaluation of patient-reported penicillin allergy labels (PALs), the utility of skin testing to the penicillin major determinant, known as penicilloyl polylysine (PPL), and to the minor determinant mixture (MDM), has been questioned. Methods: A review of a clinical antibiotic allergy database from April 2015 to December 2023 at Austin Health (Melbourne, Australia) was performed. Patients with PALs who underwent skin prick testing (SPT) and intradermal testing (IDT) to a previously-published standardised beta-lactam panel were selected. Those with positive SPT or IDT to PPL and/or MDM were identified. Results: A total of 1316 individuals were included in our analysis. Positive skin testing to any reagent was recorded for 168/1316 (12.77%). Positive results to PPL and/or MDM were recorded for 26/1316 (1.98%), including 6 with isolated positive results to PPL and/or MDM, and 20 with additional positive skin testing to at least 1 native penicillin. The number needed to test to confirm 1 additional penicillin allergy with the use of PPL and MDM was calculated at 217.39. Immediate hypersensitivities were reported by all 6 individuals testing positive to the penicillin determinants alone, including 4 with anaphylaxis. Conclusion: These results suggest limited yield in the routine inclusion of PPL and MDM in skin testing panels, particularly in evaluating delayed hypersensitivities. Restricting their use to select cohorts, such as those with anaphylaxis, may prove more efficient and cost-effective.